Construction Of A Recombinant Virus Between Poliovirus And Coxsackie A Virus 11 - Utama, Andi; Shimizu, Hiroyuki (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2005)
Recent outbreaks of circulating vaccine-derived polio virus (cVDPV) revealed the possibility of recombination between vaccine strains poliovirus (PV) and cluster C enterovirus . Based on genetic analysis, it is assumed that coxackie virus 11 (CAV-11 ), one of the cluster enterovirus, may naturally recombine with PV. To elucidate this hypothesis , the chimeric virus between PJ156, a type 1 cVDPV isolate isolated from an acute flaccid paralys is (AFP) case in the Philippines in 2001 , and CAV-11 (PJI56/CAV-11) was constructed by using long-PCR method . As the result , PJl56/CAV-11 was aviable in HEp-2 cell line. The PJl 56/CAV-11 exhibited mostly similar phenotype with parental PJ156 in term of plaque size, viral growth and neurovirulence. These results suggested that recombination between PV and CAV-11 might naturally occur during transmission of vaccine strains in the community. The effect of recombination on the viral phenotype is significantly depending on the counterpart virus Â